2017
DOI: 10.25157/jimag.v2i3.277
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS USAHATANI JAGUNG (Zea Mays L)

Abstract: 1) Mahasiswa Fakultas Pertanian Universitas Galuh2) Dosen Fakultas Pertanian Universitas Galuh 3) Dosen Fakultas Pertanian Universitas Galuh ABSTRAKPenelitian ini bertujuan untuk mengetahui (1) Kata kunci : usahatani jagung PENDAHULUANIndonesia dikenal sebagai negara agraris yang berarti negara yang mengandalkan sektor pertanian baik sebagai mata pencaharian maupun sebagai penopang pembangunan. Sektor pertanian merupakan penopang perekonomian di Indonesia karena pertanian membentuk proporsi yang sangat besar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The highest feasibility value (6.2) indicated that maize crops are planted in 85,000 plant per ha in which the balance of manure and urea dosage are at 1:1 proportion. The maize agribusiness feasibility in Indonesia is found to be 1.51 (Apriani et al, 2017); while Sumatera (Indonesia) reached an R/C ratio of 2.51 (Ginting, 2017) and 1.87 in Papua (Indonesia) (Palobo, 2019). Although it is feasible, it is lower than Pakistan's R/C ratio.…”
Section: Feasibility Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…The highest feasibility value (6.2) indicated that maize crops are planted in 85,000 plant per ha in which the balance of manure and urea dosage are at 1:1 proportion. The maize agribusiness feasibility in Indonesia is found to be 1.51 (Apriani et al, 2017); while Sumatera (Indonesia) reached an R/C ratio of 2.51 (Ginting, 2017) and 1.87 in Papua (Indonesia) (Palobo, 2019). Although it is feasible, it is lower than Pakistan's R/C ratio.…”
Section: Feasibility Analysismentioning
confidence: 93%
“…The maize planted in 85,000 plant per ha with 50% YM + 50% urea provided the farmer the highest total income as 227,941 PKR. In Indonesia, it generated total income 16,978,500 IDR and total cost 7,940,123.05 IDR with plant spacing of 75 cm x 20 cm or 65,000 plant per ha (Apriani et al, 2017).…”
Section: Financial Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Equipment depreciation is the amount of economic sacrifice that must be calculated every year from the production equipment during the production process (IDR per production process) [23]. This depreciation value is obtained from calculating the number of equipment units minus the residual value (residual value) multiplied by the price and then divided by the economic life.…”
Section: Tool Shrinkagementioning
confidence: 99%
“…Penerimaan dapat diperoleh dengan mengalikan antara jumlah produksi yang dihasilkan dengan harga jual (Irawan et al, 2020). Pendapatan dapat diperoleh dari selisih antara penerimaan yang diterima pada akhir produksi dengan total biaya yang dikeluarkan, dapat dihitung dengan rumus sebagai berikut (Apriani et al, 2017) Nilai signifikansi yang digunakan yaitu sebesar 0,05 sehingga dapat dikatakan terdapat korelasi apabila nilai signifikansi <0,05, namun sebaliknya apabila nilai signifikansi >0,05 maka dapat dikatakan bahwa tidak terdapat korelasi (Liana et al, 2022). Derajat keeratan hubungan dapat dilihat sesuai dengan pedoman pada analisis Pearson, yaitu sebagai berikut: Tabel 1.…”
Section: Metode Penelitianunclassified